2021
DOI: 10.3390/applnano2030014
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Cobalt Nanoparticles in a Simplified Food Web: From Algae to Zooplankton to Fish

Abstract: Cobalt (Co) nanoparticles (NPs) may be diffusely dispersed into natural ecosystems from various anthropogenic sources such as traffic settings and eventually end up in aquatic systems. As environmentally dispersed Co NPs may be transferred through an aquatic food web, this study investigated this transfer from algae (Scendesmus sp.) to zooplankton (Daphnia magna) to fish (Crucian carp, Carassius carassius). Effects of interactions between naturally excreted biomolecules from D. magna and Co NPs were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…Nanotechnology applications have been successfully increased [ 66 68 ]. Algae nanoparticle applications in aqua feed diets also increased due to their high of their high surface area of nanoparticles [ 69 ] which enhances growth performance, feed utilization, body composition, stress tolerance, and enhanced immune system for many species such as Nile tilapia [ 42 , 70 ], Pacific white shrimp [ 42 ], black tiger shrimp [ 57 ], and Zebrafish [ 71 ]. The current study aims to evaluate the effect of the cyanobacterium species, Arthrospira platensis NIOF17/003 nanoparticles, as a functional feed additive on growth performances, whole-body biochemical composition, blood biochemistry, steroid hormonal status, and seeds production efficiency for the Nile tilapia broodstock during the spawning cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology applications have been successfully increased [ 66 68 ]. Algae nanoparticle applications in aqua feed diets also increased due to their high of their high surface area of nanoparticles [ 69 ] which enhances growth performance, feed utilization, body composition, stress tolerance, and enhanced immune system for many species such as Nile tilapia [ 42 , 70 ], Pacific white shrimp [ 42 ], black tiger shrimp [ 57 ], and Zebrafish [ 71 ]. The current study aims to evaluate the effect of the cyanobacterium species, Arthrospira platensis NIOF17/003 nanoparticles, as a functional feed additive on growth performances, whole-body biochemical composition, blood biochemistry, steroid hormonal status, and seeds production efficiency for the Nile tilapia broodstock during the spawning cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that NPs enter aquatic environments through many sources including runoff, industrial applications and atmospheric deposition [24]. Once in the marine environment, NPs can move laterally and vertically, potentially adsorbing to organic matter [25][26][27][28], zooplankton [29,30], and other organisms [31].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple publications have shown that NP-EPS interaction occurs though it remains unclear whether NP exposure induces EPS production, e.g., as a stress response or whether the EPS production mediates shedding of NPs from the algal cell. Nevertheless, EPS is believed to play a vital role in the bioaccumulation behavior and toxicity of NPs, hence also in their potential for trophic transfer [10,11].…”
Section: Introductionmentioning
confidence: 99%